Assessing The Effectiveness Of Policing Strategies In Reducing Crime Rates In High Density Demographic Areas - Nwaogwugwu, Goodluck I.; Uwandu, Charles Ifeanyi; Ojiochie, Akaolisa Joshua; Inyekwe, Nnamdi (Journal Integration of Social Studies and Business Development, 2025)
The effectiveness of policing tactics, particularly community policing and hot spot policing, in reducing crime rates in densely populated urban areas with a diverse population is evaluated in this study. This study examines the relationship between crime rates, demographics, and policing practices using a combination of regression and correlation analysis. The results show that by encouraging trust and collaboration between law enforcement and the community, community policing is substantially linked to lower crime rates, especially violent crime. Hot spot policing, however, causes crime displacement in nearby regions even though it momentarily lowers crime in the targeted areas. Furthermore, socioeconomic factors like income levels and youth populations have a big impact on crime trends. The study highlights the importance of integrating traditional policing methods with social services, economic development, and community empowerment in order to achieve sustainable crime reduction. The results suggest that law enforcement agencies should prioritise youth initiatives, community involvement, and interagency cooperation in order to address both immediate crime problems and long-term social injustices. This study contributes to the growing body of research on crime prevention strategies and policing, providing lawmakers and law enforcement agencies in crowded cities with valuable information.